Dual Perspectives on Critical Race Theory - Muehlhoff, Tim (Christian scholar's review, 2025)
In July 2024, Timothy Muehlhoff interviewed Ed Uszynski regarding the role perspective-taking played in understanding the deep differences between Christian groups and their understanding of Critical Race Theory (CRT) as he researched and wrote his book, Untangling Critical Race Theory. This article is an edited transcript of the conversation. To listen to the full conversation, see the Winsome Conviction Podcast archives.